MATHEMATICAL MODELING OF SHRINK PROCESSES OF STEEL ON THE BASIS OF THE NAVIERSTOKES AND FOURIERKIRCHHOFF’S EQUATIONS - A. N. Chichko; S. G. Lihouzov; V. F. Sobolev; O. A. Sachek; T. V. Matyushinets; O. I. Chichko (Литьë и металлургия, 2013)
The mathematical model for simulation of process of the shrinkage porosity formation in castings, taking into account the flows convection in crystallizing metal, is offered. The numerical simulation of the temperatures fields and metal density in the process of its crystallization is carried out.